Topography measurement and reconstruction of inner surfaces based on white light interference. (December 2021) - Dong, Yuchu; Li, Zexiao; Zhu, Linlin; Zhang, Xiaodong
Highlights: A turning-path white light interferometry is built to inspect the inner surface. A novel algorithm is proposed to reconstruct the inner surface microstructure. The proposed algorithm can accurately reconstructs microstructures with large slope. Abstract: The surface topography measurement of microstructures plays a significant role in the inspection of machining quality. However, there is a lack of suitable measurement method in this requirement, especially for inner surface topography. In this paper, we built a inner surface white light interferometry with special structure, which can observe the inner surface by turning the microscopic imaging optical path. A novel composite topography reconstruction method is proposed for gaining the information with rough surface region with large slope. The Wiener filter Fourier transform method and the focus measure interference topography reconstruction method are combined to reconstruct the surface topography, the advantages of two algorithms are complemented to ensure the reconstruction accuracy of microstructure surfaces. Simulation and actual experiments are carried out, the results show that the proposed algorithm can accurately reconstruct the rough surface regions with large slope, presenting a more actual measuring effects using white light interferometry.